The impact of forestry management practices on regional economic benefits and livelihood of the rural communities in Ghana: a case study of three forest reserves in the Ashanti region - Ampadu, Prince Boateng; Yang, Jiameng (Frontiers in Forests and Global Change, 2024)
Over the past years, forests have been crucial in shaping economic development patterns by sustaining livelihoods, assisting in economic restructuring, and encouraging sustainable growth. This study assesses the impact of forestry management practices on regional economic benefits and the livelihoods of rural communities in Ghana, focusing on three forest reserves in the Ashanti Region. A mixed-method research design, incorporating both quantitative and qualitative approaches, was employed. A total of 234 respondents were purposively selected based on their availability and willingness to respond to questions, with data collected using a semi-structured questionnaire. The findings indicate a notable improvement in the standard of living, measured by four indicators: household finances, food security, physical health, and social indicators. Despite these improvements, a significant decrease in forest cover was observed in recent years. The decline in forest cover around the three forest reserves in the Ashanti Region of Ghana was attributed to poor management. Communities reported inadequate management and enforcement of forest policies, with forest managers not adhering to regulations, showing high levels of corruption, a trend consistent in 2017 (58.9%) and 2023 (60%). In summary, there has been a significant improvement in the livelihoods of rural communities around the Tano Offin, Nkrabia, and Afram Headwaters forest reserves in the Ashanti Region of Ghana. However, the management of forest resources remains poor and inefficient, leading to a substantial loss of forest cover. This loss threatens biodiversity and ecosystem services. The government should implement proactive forestry management strategies and promote community-based approaches to enhance community involvement in managing their forest resources.